2009
DOI: 10.1186/cc8208
|View full text |Cite
|
Sign up to set email alerts
|

Th1 and Th17 hypercytokinemia as early host response signature in severe pandemic influenza

Abstract: IntroductionHuman host immune response following infection with the new variant of A/H1N1 pandemic influenza virus (nvH1N1) is poorly understood. We utilize here systemic cytokine and antibody levels in evaluating differences in early immune response in both mild and severe patients infected with nvH1N1.MethodsWe profiled 29 cytokines and chemokines and evaluated the haemagglutination inhibition activity as quantitative and qualitative measurements of host immune responses in serum obtained during the first fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

28
333
6
12

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 340 publications
(382 citation statements)
references
References 35 publications
28
333
6
12
Order By: Relevance
“…Both intranasal vaccination 43 and influenza virus challenge 44 , 45 have previously been shown to induce a strong IL‐17 response in mice; however, the exact role of IL‐17 in the pathogenesis of influenza is not yet clear. Recent reports suggest a role for IL‐17 in inducing a protective immune response against influenza viral challenge in mice 45 , 46 and also in patients with severe pandemic H1N1 influenza 47 . In contrast, Crowe et al.…”
Section: Discussionmentioning
confidence: 99%
“…Both intranasal vaccination 43 and influenza virus challenge 44 , 45 have previously been shown to induce a strong IL‐17 response in mice; however, the exact role of IL‐17 in the pathogenesis of influenza is not yet clear. Recent reports suggest a role for IL‐17 in inducing a protective immune response against influenza viral challenge in mice 45 , 46 and also in patients with severe pandemic H1N1 influenza 47 . In contrast, Crowe et al.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with outpatients, the inflammatory response to severe influenza A (H1N1) is more pronounced in patients with severe disease who require hospitalization, and the response can be observed even in patients who do not have bacterial superinfection. 12 The ability of the influenza and other acute respiratory viruses to provoke microvascular alterationscharacterized by sludge of capillary flow associated with hypercoagulability and increased blood viscosity-has been suggested by others. 28 Therefore, significant microcirculatory perfusion deficits could be an important pathophysiological mechanism in severe influenza A (H1N1) infections.…”
Section: Steroidsmentioning
confidence: 97%
“…11 This proinflammatory response is not restricted to the lungs. Recently, Bermejo-Martin et al 12 reported that systemic levels of several pro-inflammatory cytokines were increased in patients hospitalized with H1N1 infection, especially in those who were critically ill. Remote organ dysfunction may also be observed, including elevated liver enzymes, rhabdomyolysis, renal failure, and shock.…”
Section: Résumémentioning
confidence: 99%
“…Previous clinical reports analyzing sera obtained from 29 patients in Spain and 57 patients in Hong Kong showed that Th-1 and Th-17 hypercytokinemia is an early host response signature in severe cases of 2009 pandemic influenza [6,8]. However, controversy regarding the role of the Th-17 response was raised by a npg recent study from a Romanian group reporting cytokine responses in 32 patients with severe H1N1 influenza A virus infection [7].…”
Section: Cytokine Responses In Patients and Mice Infected With 2009 Hmentioning
confidence: 99%
“…Altogether, these data suggest that the 2009 H1N1 strain is still circulating in the world. Previous clinical reports indicated that hypercytokinemia is involved in the pathology of severe 2009 pandemic influenza [6][7][8]. However, the underlying molecular mechanism is unclear.…”
Section: Introductionmentioning
confidence: 99%